The Construction of Writing Identity: An Analysis in Dissertation Writing - Wijayatri, Lucia Yeni (British (Jurnal Bahasa dan Sastra Inggris), 2024)
The insights from studies on self-identity construction in writing have encouraged linguistics scholars to continuously explore the presence of writers’ identity in writing. Nevertheless, due to arguments that question whether second language writers construct their identity in writing as well since they are still in tension between fulfilling the writing’s expectation and their English proficiency, a particular study that explores second language writing identity is needed. This study, therefore, was conducted to explore how second language writers construct their identity, particularly in academic writing. A dissertation written by an Indonesian doctoral candidate was chosen to be the main source of data. Adopting the work of Ivanic and Camps (2001), this study employed the three language functions proposed by Halliday, i.e., ideational function, interpersonal function, and textual function, as the analytical tools. Each function was broken down into specific features by which the texts were identified. Then, to sharpen the existence of writers’ identity in writing, the findings were identified to find the manifestation of the four aspects of identity proposed by Ivanic (1998). Based on the results of the analysis, this study found that writers’ identities are presented beyond the linguistic discourse employed in the writings. Then, regarding the manifestation of each function in the four aspects of writing identity, this study revealed that all aspects were manifested in the three language functions. It puts forward an argument that writing is the act of identity, and even a second language writer constructs her writing identity, including in an academic one. The study also found that even a second language writer establishes her own identity, which conforms to the common convention in academic writing.  Keywords: writing identity, second language writers, academic writing